Evaluating the significance of expression of CEA mRNA and levels of CEA and its related proteins in colorectal cancer patients. Issue 5 (25th November 2013) - Wang, Wenyuan; Li, Yaoping; Zhang, Xin; Jing, Jiexian; Zhao, Xianwen; Wang, Yan; Han, Cunzhi
Abstract Objective To explore the clinical significance of expression of CEA mRNA and serum CEA and the related proteins in colorectal cancer (CRC). Methods Blood samples were collected from 370 CRC patients and 350 controls. CEA mRNA was determined by RT‐PCR and levels of CEA, CA19‐9, CA242, and CA724 were examined with chemiluminescence. Results The positive rate of jointly detecting serum CEA, CA19‐9, CA242, and CA724 was significantly higher than CEA mRNA expressions (P < 0.01), both positive rates were significantly correlated with TNM stage, lymph node, and visceral metastasis. The positive rate of jointly detecting in patients with poorly differentiated tumor was significantly higher than that in patients with highly differentiated tumor (P < 0.01). By contrast, CEA mRNA expression was not related with histopathologic grading. Postoperative follow‐up found that all patients with high levels of CEA mRNA and serum CEA and the related proteins had liver, lung, pelvis, or other distant metastases. Conclusions These results suggest that high expressions of CEA mRNA and high levels of serum CEA and the related proteins are associated with the incidence and advanced of CRC. In addition, joint detection of serum CEA and the related proteins is more sensitivity than examination of serum CEA mRNA. J. Surg. Oncol. 2014 109:440–444. © 2013 Wiley Periodicals, Inc.